ASSESSMENT OF CONSUMER AWARENESS ON FOOD LABELS AND THE EFFECT OF THE LEVEL OF AWARENESS ON BUYING BEHAVIOUR OF CONSUMERS IN JAFFNA DISTRICT - Simmaky, S.; Vasantharuba, S.; Madhujith, T. (My University, 2015)
Food labels present a set of vital information such as date of expiry, nutritional data to the consumers which influence their purchasing. The present study was conducted to assess the awareness on food labels and the effect of the level of awareness on the buying behaviour of consumers in Jaffna district. A questionnaire was used to collect information from a random sample of 260 consumers purchasing pre-packaged foods at super markets and retail shops in Jaffna district. The data were analysed using SPSS Package to determine associations between various socio-demographic factors and the use of food label information. It was found that 92% of the Jaffna consumers are aware of the information provided on the food labels.89.5% of participants considered the dates of expiry and manufacture were the most important information. The percent participants considered , list of Ingredients, nutritional information, instructions for use, health warnings and health claims were 60.3%, 59%, 51.9%, 49.4% and 46.9%respectively. It is noteworthy that the consumers assigned less importance to the country of origin, special food characteristics and serving size (47.7%, 39.3% and 35.6%, respectively). Awareness and use of food label information were significantly associated with level of income, age, occupation and level of education of respondents. The respondents with high monthly income, professionals, of old age (>65 age) and postgraduates identified nutritional information, health claims and health warnings as the most important labelling parameters. Consumers placed high importance for price (53.5%) and brand (43.1%) of the products. Brand is highly preferred by 15-25 years age groups and by graduates and postgraduate students. Low income group paid more attention to price of the product. The outcomes of the study are helpful for food companies in deciding which type of information placed on the food labels influence the consumers most in making rational food choice
Keywords: Awareness; Consumers; Food Label